"y' + xy = {y^2}{e^{\\frac{{{x^2}}}{2}}}\\cos x"
Let
"y = uv \\Rightarrow y' = u'v + uv'"
Then
"\\begin{array}{l}\nu'v + uv' + xuv = {u^2}{v^2}{e^{\\frac{{{x^2}}}{2}}}\\cos x\\\\\nu'v + u\\left( {v' + xv} \\right) = {u^2}{v^2}{e^{\\frac{{{x^2}}}{2}}}\\cos x\n\\end{array}"
Let
"v' + xv = 0 \\Rightarrow \\frac{{dv}}{{dx}} = - xv \\Rightarrow \\frac{{dv}}{v} = - xdx \\Rightarrow \\ln v = - \\frac{{{x^2}}}{2} \\Rightarrow v = {e^{ - \\frac{{{x^2}}}{2}}}"
Then
"u'{e^{ - \\frac{{{x^2}}}{2}}} = {u^2}{e^{ - {x^2}}}{e^{\\frac{{{x^2}}}{2}}}\\cos x"
"\\begin{array}{l}\nu' = {u^2}{e^{ - {x^2}}}{e^{{x^2}}}\\cos x\\\\\nu' = {u^2}\\cos x\n\\end{array}"
"\\begin{array}{l}\n\\frac{{du}}{{dx}} = {u^2}\\cos x\\\\\n\\frac{{du}}{{{u^2}}} = \\cos xdx\\\\\n - \\frac{1}{u} = \\sin x - C\\\\\nu = \\frac{1}{{C - \\sin x}}\n\\end{array}"
"y = uv = \\frac{{{e^{ - \\frac{{{x^2}}}{2}}}}}{{C - \\sin x}}"
Answer: "y = \\frac{{{e^{ - \\frac{{{x^2}}}{2}}}}}{{C - \\sin x}}"
Comments
Leave a comment